Developing Opioid Prescription Guidelines After Anorectal Surgery: Do Patient-Reported Outcomes and Risk Factors Influence Consumption?. Issue 11 (23rd November 2021) - Althans, Alison R.; Hrebinko, Katherine; Olaitan, Oluwatosin; Ettore, Maria A.; Cunningham, Kellie E.; Celebrezze, James P.; Medich, David S.; Holder-Murray, Jennifer
Abstract : BACKGROUND: Opioids prescribed to address postoperative pain drive opioid-related deaths in the United States. Prescribing guidelines have been developed for many general surgical procedures, which have decreased opioid prescription and consumption. The literature on opioids after anorectal surgery is lacking. OBJECTIVE: We analyzed our data on opioid prescription and consumption to create opioid-prescribing guidelines for anorectal procedures. DESIGN: We designed a prospectively collected postoperative survey given to consecutive patients undergoing anorectal surgery by colorectal surgeons. SETTINGS: Patients had surgery at 2 academic, university-affiliated hospitals. PATIENTS: Patients undergoing anorectal surgery from May 3, 2018, to December 18, 2019, were included in the study. Patients were excluded if they were <18 years of age, had a concurrent abdominopelvic surgery, consumed opioids in the week before their operation, or were without follow-up at 3 months postoperatively. MAIN OUTCOME MEASURES: The primary outcome of this study was the number of opioid pills needed to fulfill consumption of 80% of patients. Secondary outcome measures were patient, operative, and postoperative factors associated with increasing pill consumption. RESULTS: Eighteen 5-mg oxycodone tablets were needed to fulfill the needs of 80% of patients. An overall median of 8 pills was consumed. Pill prescription was independently predictive of increased consumption. The only patient factor associated with increased consumption was race; no other patient or operative factors were predictive of consumption. LIMITATIONS: Limitations of this study include its partially retrospective nature, use of self-reported data, and lack of racial diversity among our cohort. CONCLUSIONS: Without any clinical factors predictive of increased consumption, prescription guidelines can be standardized to ≤18 5-mg oxycodone tablets across anorectal surgery patients. As prescription is correlated with consumption, further work is needed to determine whether lesser quantities of opioids prescribed offer similar postoperative pain relief for patients undergoing anorectal surgery. See Video Abstract at http://links.lww.com/DCR/B821 . DESARROLLO DE PAUTAS PARA LA PRESCRIPCIÓN DE OPIOIDES DESPUÉS DE CIRUGÍA ANORRECTAL: ¿INFLUYEN EN EL CONSUMO LOS RESULTADOS INFORMADOS POR EL PACIENTE Y LOS FACTORES DE RIESGO? ANTECEDENTES: Los opioides recetados para tratar el dolor posoperatorio provocan muertes relacionadas con los opioides en los Estados Unidos. Se han desarrollado pautas de prescripción para muchos procedimientos quirúrgicos generales y estas han conducido a una disminución de la prescripción y el consumo de opioides. Hay una carencia de literatura sobre el uso de opioides después de cirugía anorrectal. OBJETIVO: Analizamos nuestros datos sobre prescripción y consumo de opioides para crear pautas de prescripción de opioides para procedimientos anorrectales. DISEÑO: Diseñamos una encuesta postoperatoria recopilada prospectivamente que se administró a pacientes consecutivos sometidos a cirugía anorrectal por cirujanos colorrectales. AJUSTES: Los pacientes fueron operados en dos hospitales académicos afiliados a la universidad. PACIENTES: Se incluyeron en el estudio pacientes sometidos a cirugía anorrectal desde el 3/05/2018 hasta el 18/12/2019. Se excluyó a los pacientes que tenían menos de 18 años, a los que se sometieron a cirugía abdominopélvica concurrente, a los que consumieron opioides en la semana anterior a la operación, o si no tenían seguimiento a los 3 meses del postoperatorio. PRINCIPALES MEDIDAS DE DESENLACE: El desenlace principal de este estudio fue el número de píldoras de opioides necesarias para satisfacer el consumo del 80% de los pacientes. Las medidas de desenlace secundarias fueron los factores del paciente, operatorios y posoperatorios asociados con el aumento del consumo de píldoras. RESULTADOS: Fueron necesarios dieciocho comprimidos de oxicodona de 5 mg para cubrir las necesidades del 80% de los pacientes. Se consumió una mediana general de 8 píldoras. La prescripción de la píldora fue un predictor independiente de un mayor consumo. El único factor del paciente asociado con un mayor consumo fue la raza; ningún otro paciente o factores operativos fueron predictivos del consumo. LIMITACIONES: Las limitaciones de este estudio incluyen su naturaleza parcialmente retrospectiva, el uso de datos autoinformados y la falta de diversidad racial entre nuestra cohorte. CONCLUSIONES: Sin ningún factor clínico que prediga un aumento del consumo, las pautas de prescripción se pueden estandarizar a dieciocho o menos comprimidos de oxicodona de 5 mg en pacientes sometidos a cirugía anorrectal. Como la prescripción se correlaciona con el consumo, se necesita más trabajo para determinar si cantidades menores de opioides prescritos ofrecen un alivio del dolor posoperatorio similar para los pacientes sometidos a cirugía anorrectal. Consulte Video Resumen en http://links.lww.com/DCR/B821 . (Traducción—Juan Carlos Reyes )